Epidemiology of ocular trauma in the Indigenous vs non‐Indigenous population in the Top End. (22nd November 2018) - Kennedy, Morgan S.; Robinson, James; Whist, Eline; McCallum, Gabrielle B.; Mahendrarajah, Tharmalingam
Abstract : Importance: Epidemiological data on visually significant ocular trauma in the Top End of the Northern Territory. Background: Our main objective is to determine whether Indigenous patients are disproportionately affected by visually significant ocular trauma as compared to non‐Indigenous patients. Design: This was a retrospective audit at the Royal Darwin Hospital in the Top End of the Northern Territory during January 2013 to June 2015. Participants: A total of 104 ocular trauma patients were included; 43 were Indigenous and 61 were non‐Indigenous. Methods: Medical records of patients with ocular trauma between January 2013 and June 2015 (except simple, non‐penetrating corneal foreign bodies and abrasions) were reviewed. Vision loss was defined by visual acuity: mild ≥6/18, moderate 6/18‐6/60, severe ≤6/60 following World Health Organization standards. Main Outcome Measures: The study included the incidence of ocular trauma patients by ethnicity (Indigenous vs non‐Indigenous). Our secondary outcome included vision loss, mechanism of injury, open vs closed injury, age, remoteness and alcohol involvement. Results: A total of 104 patient charts were reviewed; 43 (41%) were Indigenous and 61 (59%) were non‐Indigenous. Alleged assault was the greatest contributor to ocular trauma in both groups (74% in Indigenous vs 39% non‐Indigenous). Severe vision loss was more prevalent in the Indigenous vs non‐Indigenous patients (30% vs 16%). Conclusions and Relevance: Indigenous patients were disproportionately affected by visually significant ocular trauma compared to non‐Indigenous patients. This research provides important data on ocular trauma in the Northern Territory. Further prevention strategies are needed to reduce vision loss in this population.